DOS ESPECIES DE DICTYOPHYLLUM DEL TRIASICO DE PASO FLORES, PROVINCIA DE NEUQUEN, ARGENTINA (Ameghiniana, 2013)
Two species of Dictyophyllum (Dipteridaceae) from the Upper Triassic "Paso Flores Series" are recorded for the first time. An emended diagnosis is given for Dictyophyllum tenuifoliu.m Stipanicic & Menendez, and the geographical distribution of D. spectabile. a rare North-European and Japanese species is extended to South America.